The Salter innominate osteotomy does not lead to acetabular retroversion. Issue 6 (November 2021) - Airey, Grace; Shelton, James; Dorman, Sara; Bruce, Colin; Wright, David M.
Abstract : In children with developmental dysplasia of the hip (DDH), Salter's innominate osteotomy aims to surgically manipulate the acetabulum to increase anterior coverage and aid joint support. Consequently, this procedure may retrovert the acetabulum, predisposing patients to pain, osteoarthritis, impingement, or further surgical intervention. In this study, we aim to address whether the innominate osteotomy leads to acetabular retroversion postoperatively or at follow-up. Ninety-two patients were identified from our institutions DDH database between 2009 and 2016, who underwent a unilateral innominate osteotomy for DDH, performed by expert surgeons in a leading paediatric hospital. A novel technique was utilized to measure acetabular version on postoperative computed tomography (CT) scans, where acetabular version was compared between the pathological and contralateral control hips. Measurement of acetabular version in postoperative and control hips demonstrated no incidence of acetabular retroversion. A significant difference was observed when comparing the acetabular version of control versus post-operative hips ( P < 0.001), where hips postinnominate osteotomy had a larger degree of acetabular anteversion compared to the control hip. Furthermore, on follow-up radiographic imaging, there was no evidence of acetabular retroversion when using previously defined markers. This study confirms that the Salter innominate osteotomy does not lead to acetabular retroversion both immediately post-operatively and throughout follow-up. In fact, it demonstrates that the acetabula are more anteverted than the contralateral control hip, which has not been previously documented. Additionally, this study demonstrates a novel method of measuring acetabular retroversion using CT technology that adjusts for pelvic tilt, which is repeatable among individuals.